1999
DOI: 10.1016/s0735-1097(99)00207-7
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of troponin T and troponin I as predictors of cardiac events in patients undergoing chronic dialysis at a Veteran’s Hospital: a pilot study

Abstract: This prospective pilot study clearly delineates the troponins as important prognosticators in asymptomatic otherwise "stable" patients on chronic dialysis, especially those with concomitant diabetes mellitus. It also appears that troponins are more likely to be elevated in dialysis patients than other patients with renal failure not on dialysis. The above suggests that the combination of cTnI and cTnT might be very effective in elucidating cardiac risks of patients with renal failure undergoing chronic dialysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
51
0
1

Year Published

2001
2001
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(58 citation statements)
references
References 25 publications
5
51
0
1
Order By: Relevance
“…Recentlymyocardial troponin T has increasingly been used as a well-established indicator for diagnosing myocardial infarction (Roppolo et al 1999). Investigations by Senaratne et al (2000) revealed that hyperhomocysteinemia is associated with an increased risk of cardiovascular diseases independently of classical risk factors.…”
Section: Discussionmentioning
confidence: 99%
“…Recentlymyocardial troponin T has increasingly been used as a well-established indicator for diagnosing myocardial infarction (Roppolo et al 1999). Investigations by Senaratne et al (2000) revealed that hyperhomocysteinemia is associated with an increased risk of cardiovascular diseases independently of classical risk factors.…”
Section: Discussionmentioning
confidence: 99%
“…Recent molecular biological studies have elucidated the relation between cytokines evoked by activated macrophages and plaque vulnerability.-Inflammation causes imbalance between fibrous cap degradation and repair. *O Several clinical observations have established a quantitative relationship between the degree and level of inflammation and the clinical outcome in symptomatic and asymptomatic patients with coronary artery disease.l6, 179 21 However, data correlating the markers of inflammation with angiographic anatomy are scarce. Our study confirms previous observations relating inflammation and need for revasc~larization.…”
Section: Discussionmentioning
confidence: 99%
“…For CKD patients who are not receiving dialysis, data are limited and conflicting. [18][19][20] To our knowledge, this is the first study to document the relatively high prevalence of increased cTnT with the degree of renal failure in pre-dialyzed patients. In this study, we demonstrated that there are significant elevations of troponin levels with renal function parameters in CKD patients.…”
Section: Discussionmentioning
confidence: 79%